2009
DOI: 10.1007/s00394-009-0778-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and insulin responses to whole grain breakfasts varying in soluble fiber, β-glucan

Abstract: These data suggest that acute consumption of 10 g of beta-glucan is able to induce physiologically beneficial effects on postprandial insulin responses in obese women at risk for insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…The soluble fiber content (i.e., β-glucan) of the barley and oat muffins in the present intervention ranged from 2.4–3.2 g. Interestingly, Kim et al [43] reported a barley breakfast providing ≥10 g β-glucan was necessary to observe a beneficial effect on glycemic response in obese women who were at increased risk of developing insulin resistance. In addition to the effect of dose, the effect of cooking or baking of whole grains may alter the physiological effects of soluble fiber; e.g., Kerckhoffs et al [44] found when oats are baked into bread or cookies, the β-glucan naturally found in oats becomes less viscous than raw β-glucan.…”
Section: Discussionmentioning
confidence: 76%
“…The soluble fiber content (i.e., β-glucan) of the barley and oat muffins in the present intervention ranged from 2.4–3.2 g. Interestingly, Kim et al [43] reported a barley breakfast providing ≥10 g β-glucan was necessary to observe a beneficial effect on glycemic response in obese women who were at increased risk of developing insulin resistance. In addition to the effect of dose, the effect of cooking or baking of whole grains may alter the physiological effects of soluble fiber; e.g., Kerckhoffs et al [44] found when oats are baked into bread or cookies, the β-glucan naturally found in oats becomes less viscous than raw β-glucan.…”
Section: Discussionmentioning
confidence: 76%
“…Human randomized trials have demonstrated that moderate alcohol consumption improved insulin sensitivity[28] and increased plasma levels of adiponectin[28]. Likewise, weight reduction[29]and dietary intervention[30] have been associated with improved insulin sensitivity…”
Section: Discussionmentioning
confidence: 99%
“…1). Kim and others (33) reported that higher amount of beta-glucan consumption induced a reduced peak and sustained net increment in the late phase (60 and 120 min) of postprandial glucose response in obese women with increased risk for insulin resistance. Tapola and others (34) reported that oat bran flour high in beta-glucan acted as an active ingredient decreasing postprandial glycemic response of an oral glucose load in subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%